Interpersonal brain synchronization during sensorimotor synchronization in people with different aerobic fitness levels: A fNIRS-based hyperscanning study. - Zixin Wang; Chengliang Wang; Shilin Wen; Haoteng Yuan; Shengyu Dai; Jianguang Cai; Liang Jiang; Xue Chen; Xianzhi Gao; Hui Xu (PLoS ONE)
Sensorimotor synchronization (SMS) refers to the temporal coordination of individual actions with perceptible external events and rhythms. Previous research has revealed a potential relationship between SMS abilities and physical activity, with proposed links to underlying inner-brain cognitive processes. However, it needs to be explored that whether good aerobic fitness will have a strong SMS ability, its internal mechanism, and the inter-brain mechanism. In the present study, we recruited 23 dyads of long-distance runners as the experimental group and 22 dyads of non-physical education major students as the control group. Participants were required to perform a dyadic finger-tapping synchronization task. During task performance, neural activities were recorded in frontal area by the functional near-infrared spectroscopy (fNIRS)-based hyperscanning approach. The results revealed that the experimental group demonstrated superior SMS abilities in the seconds-scale task. This advantage was attributed to their enhanced stability. Importantly, significant interpersonal brain synchronization(IBS) in the right superior frontal gyrus (rSFG) was observed only in the experimental group during SMS task performance, and this IBS was associated with their superior stability. These findings provide new evidence supporting the relationship between physical activity, cognitive capabilities, and associated neural plasticity.